F, D LITERATURE REVIEW: IMPLEMENTASI E-LKPD BERNUANSA ESQ DALAM PEMBELAJARAN SISTEM PENCERNAAN DILENGKAPI TEKA-TEKI SILANG DI SMA/ MA - Daely, Fatina; Lufri, Lufri (LP2M IAIN Ambon, 2025)
Education in the 21st century requires a systematic and innovative approach to develop students' character and intellect. This study aims to analyze the implementation of E-LKPD with Emotional Spiritual Quotient (ESQ) nuances in learning the digestive system equipped with crossword puzzles in SMA/MA. Using the literature review method, this study collected and analyzed 10 articles published between 2021 and 2025. The results showed that the E-LKPD developed had high validity and practicality, and had a positive impact on student learning outcomes, both in cognitive, affective, and psychomotor aspects. In addition, the integration of emotional and spiritual values in E-LKPD can increase students' awareness of the importance of EQ and SQ in everyday life. This study concludes that the application of E-LKPD with ESQ nuances not only improves students' intellectual abilities, but also supports the development of their character and morality in society.